Parâmetros clínico-laboratoriais associados ao óbito em pacientes neonatos em uso de vancomicina - Oliveira, Thaís Barbosa de (2024)
Neonatal sepsis is characterized as the manifestation of signs of infection in patients in the first month of life and is a major challenge in clinical management, with high mortality rates. Its pharmacological treatment is complex and must take into account the sensitivity of the microorganism and the general condition of the patient. Vancomycin is an important drug in this context, indicated as the first choice for the treatment of infections caused by methicillin-resistant Staphylococcus aureus. Due to its narrow therapeutic window, it requires therapeutic monitoring during treatment, aiming to optimize therapeutic effects and minimize toxicity. Laboratory tests are essential to monitor the clinical evolution of newborns undergoing antibiotic therapy with vancomycin. Therefore, the present study aimed to evaluate the clinical and laboratory changes associated with death in neonatal patients using vancomycin. This is a retrospective cohort research, involving analysis of serum vancomycin monitoring in 57 neonatal patients admitted to a reference maternity hospital in the state of Ceará, from January to July 2021. Data were collected relating to clinical parameters, results of laboratory tests and patient death outcomes through physical and digital records. Among the total of 57 newborns (NBs), 32 (56%) were female and 25 (44%) were male. Regarding birth weight classification, 28 newborns were classified as extremely low birth weight (49%) (<1.000 g) and 12 as very low weight (21%) (≥1.000 g <1.500 g). The majority of newborns were prematurity, with 23 classified as moderately preterm (≥ 28 and < 34 weeks) (40%) and 18 as extremely preterm (32%) (< 28 weeks). Regarding the clinical outcome, it was observed that 33% of newborns died. It was observed that patients with vancokinemia levels below the therapeutic window showed an increase in neutrophil counts (p= 0.0122) and vancokinemia levels above the therapeutic window showed an increase in serum creatinine levels (p= 0.0152). A significant correlation of moderate strength was observed between serum creatinine and vancomycin concentrations (r = 0.5822; p = 0.0007). Still in this sense, the ROC curve showed that the analysis of serum creatinine helps in predicting altered levels of vankokinemia (AUC= 0.7813; p<0.05). In this context, several clinical and laboratory factors can be predictors of severity or outcome in newborns using vancomycin; in the present study, death was associated with low birth weight (p = 0.008), reduced head circumference (p = 0.038), thrombocytopenia (p = 0.038), hypocalcemia (p = 0.004) and vankokinemia above 15 μg/mL ( p = 0.0147). Considering laboratory parameters, binary logistic regression analysis revealed that changes in creatinine levels, whether or not associated with high vancokinemia, were predictors of death in the patients studied. These data may assist in the clinical management of newborns using vancomycin and direct scientific research aimed at developing effective and safe therapeutic strategies.